Risk factors influencing postpartum depression among women attending postnatal clinic at Komfo Anokye Teaching Hospital, Kumasi, Ghana. - Buabeng, Akua Afriyie (2016)
A thesis submitted to the Department of Population, Family & Reproductive Health College of Health Sciences, School of Public Health, in partial fulfillment of the requirements for the degree of Master of Public Health in Population, Family and Reproductive Health, 2015